Insight on the anatomy, systematic relationships, and age of the Early Cretaceous ankylopollexian dinosaur Dakotadon lakotaensis - Boyd,Clint A.; Pagnac,Darrin C. (PeerJ, 2015)
Knowledge regarding the early evolution within the dinosaurian clade Ankylopollexia drastically increased over the past two decades, in part because of an increase in described taxa from the Early Cretaceous of North America. These advances motivated the recent completion of extensive preparation and conservation work on the holotype and only known specimen of Dakotadon lakotaensis, a basal ankylopollexian from the Lakota Formation of South Dakota. That specimen (SDSM 8656) preserves a partial skull, lower jaws, a single dorsal vertebra, and two caudal vertebrae. That new preparation work exposed several bones not included in the original description and revealed that other bones were previously misidentified. The presence of extensive deformation in areas of the skull is also noted that influenced inaccuracies in prior descriptions and reconstructions of this taxon. In addition to providing an extensive re-description of D. lakotaensis, this study reviews previously proposed diagnoses for this taxon, identifies two autapomorphies, and provides an extensive differential diagnosis. Dakotadon lakotaensis is distinct from the only other ankylopollexian taxon known from the Lakota Formation, Osmakasaurus depressus, in the presence of two prominent, anteroposteriorly oriented ridges on the ventral surfaces of the caudal vertebrae, the only overlapping material preserved between these taxa. The systematic relationships of D. lakotaensis are evaluated using both the parsimony and posterior probability optimality criteria, with both sets of analyses recovering D. lakotaensis as a non-hadrosauriform ankylopollexian that is more closely related to taxa from the Early Cretaceous (e.g., Iguanacolossus, Hippodraco, and Theiophytalia) than to more basally situated taxa from the Jurassic (e.g., Camptosaurus, Uteodon). This taxonomic work is supplemented by field work that relocated the type locality, confirming its provenance from unit L2 (lower Fuson Member equivalent) of the Lakota Formation. Those data, combined with recently revised ages for the members of the Lakota Formation based on charophyte and ostracod biostratigraphy, constrain the age of this taxon to the late Valanginian to early Barremian.
Keywords: Dakotadon; Lakota Formation; Early Cretaceous; Ornithischia; Ankylopollexia; South Dakota; Bayesian; Systematics